Avaliação dos efeitos do envelhecimento em superfícies seletivas solares de CrxOy obtidas a partir de processo de eletrodeposição - Gonçalves, Ronny Peterson da Nóbrega (2021)
Solar energy is abundant, clean and has the greatest potential to be the main energy source for the whole of society. Although some countries already include solar conversions in their energy matrices, this technology is still not very accessible, especially in developing countries like Brazil. One of the main components used in solar thermal conversion is the Solar Collector. The cheapness of these, aiming at their greater dissemination, depends mainly on the increase of their life service and their efficiency, which can be achieved through the Solar Selective Surfaces (SSS). SSS are coatings with good absorption of solar radiation and good reflectivity of infrared radiation, avoiding energy losses from the emission phenomenon. The electroplating of black chromium is a low-cost process that makes it possible to obtain SSS with good optical characteristics and thermal stability at the beginning of its life service. However, little has been discussed about the aging of these surfaces and how their properties are affected throughout their lives. This study sought to evaluate the behavior of these surfaces when subjected to accelerated aging processes. 128 films were deposited on stainless steel substrates that underwent 4 different surface treatments using different electrodeposition parameters. The samples were submitted to a customized aging test and characterized using Spectrophotometry in UV-Vis and Infrared, Optical Profilometry, Scanning Electron Microscopy and X-Ray Diffraction. For the non-aged samples, it was observed that the E6 film (electropolished substrate, 60 s, 30 mm) presented the best absorption performance (97.76%). It was observed that the longer electrodeposition times and the shorter working distance made it possible to obtain the best optical and morphological characteristics. It was noted that the optical properties were improved after aging at 300ºC, resulting from the formation of Cr2O3 in the films. Evidence was found that optical traps were formed since the rougher films showed, in general, greater absorptances.